PENERIMAAN PANELIS DAN ANALISIS USAHA ES KRIM SOYGHURTYANG MENGANDUNG Lactobacillus acidophilus TERENKAPSULASI - Perdana, Mazhar; Efendi, Raswen; Yusri, Jumatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The porpose of study was to determine the level of panelistsacceptance and analysis of business by ice cream soyghurt the encapsulated Lactobacillus acidophilus. The study began with the manufacture of encapsulated Lactobacillus acidophilus and proceed with the making of ice cream soyghurt then tested by comparing the reception panelists soyghurt encapsulation ice cream and yoghurt ice cream commercial. The result of T test analysis showed that soyghurtencapsulation ice cream and yoghurtice cream commercial significantly different (P<0.05) on the attributes of flavor, texture and color, while the smell and flavor attributes were not significantly different (P>0.05). Chi Squared results show that there is a difference between soyghurt encapsulation ice cream and yoghurtice cream commercial. The analysis of business shows the soyghurt encapsulationice cream able to compete with commercial yoghurt ice cream on the market. Keywords: Soyghurt, Yoghurt, Analysis ofbusiness and Acceptance panelists.